Proposta de composição de custos unitários e orçamentos de serviços em vias não pavimentadas - Santana, Luiz Antonio Ferreira de (2006)
This master paper is about a proposal of unit costs composition for a system of alternatives related to the interventions of the faults that might affect unpaved roads. It is carried out a theoretical approach on these roads, concerning specially to the kinds of possible faults that might affect unpaved roads performance. It is analyzed the importance of a Pavement Management System implementation, specially as for its benefit for controlling the roads conditions in study. The description of the costs which are involved in the intervention services of a unpaved road deals with a financial study that is involved in this process, specifically as for direct and indirect costs regarding the composition of unit ones. Planning to reach this paper objectives, it has been considered the parameters of services and prices from some organizations that have worked with related activities, specially those ones dealt by SICRO2. The intervention and faults proposals suggested by previous work were analysed as well as it was carried out other suggestions for solving these possible faultson unpaved roads. Through the alternatives of solutions which were presented in this paper, it is suggested a proposal for the composition of unit costs concerning those services that might be carried out within unpaved road intervention processes.